Genetic and environmental contribution to social dominance orientation and its overlap with HEXACO personality traits : a twin study - Bratko, Denis (Array, 2021)
Social dominance orientation (SDO), i.e. the preference toward egalitarian or hierarchically arranged relations within a society may be studied from social/contextual, but also dispositional perspective. The aim of the present study was to explore genetic and environmental contribution to the individual differences in SDO, and its overlap with HEXACO personality traits, both at phenotypic and latent genetic and environmental levels. The sample consisted of 830 Croatian twins aged 19 to 28 years who filled-in the self-report measures. Data analyses indicated the heritability of SDO was over 40%, with no evidence for the common environmental influences. SDO phenotypic variance substantially overlapped with Honesty-Humility, Emotionality, and Openness domains. Numerous significant correlations were found at the facet level, with the highest phenotypic overlap for the "interstitial" altruism facet. However, incremental predictive power of personality (over age and sex) was moderate: 13% and 19% of the phenotypic SDO variance was predicted by HEXACO traits at the domains and facet levels, respectively. Multivariate behavioural genetic analysis indicated that 19% and 3% of the genetic and unique environmental variance of SDO overlapped with the genetic and unique environmental variance of personality, respectively. Substantial genetic correlations of SDO with Honesty-Humility and Openness domains were found, while marginal unique environmental correlation was found for Openness domain only. The etiological overlap between SDO and personality represents an argument in favour of taking dispositional along with social/contextual perspective in explaining social behaviour.